Transportation of Fe3O4-SiO2-Al2O3/EO and SiO2-Al2O3/EO nanoparticles in magnetized Reiner–Philippoff liquid, including modified fluxes via Galerkin algorithm: Significance of EMHD - Sohail, Muhammad; Nazir, Umar; Mukdasai, Kanit; Singh, Manoj; Singh, Abha; Mohan, Chandika Rama; Galal, Ahmed M.; Eldin, Sayed M. (Frontiers in Physics, 2023)
In this article, developing study is focused on mass diffusion and thermal energy enhancement in Reiner Philippoff martial across vertical-surface under exposed Lorentz force. Characterizations regarding thermal energy and mass diffusion are modified utilizing non-Fourier’s theory in the presence heat source. Three types of nanoparticles called 〖Al〗_2 O_3, titanium dioxide and 〖TiO〗_2 in egine oil are inserted for production of heat energy. Darcy’s Forchheimer theory is used to analyze behavior flow and heat energy. Moreover, effects related to Dufour and Soret are added. Transformed system of ODEs is achieved regarding the developed model using similarity variables. Numerically developing model in form of ODEs is handled with the aid of finite element method (FEM). Fluidic thermal energy is augmented against upshot values of time relaxation number. Fluidic concentration is declined against change in Schmidt number as well as chemical reaction parameter.